2018
DOI: 10.1111/ctr.13437
|View full text |Cite
|
Sign up to set email alerts
|

Echinocandin use in lung transplant recipients

Abstract: Background Invasive fungal infections (IFI) are associated with significant morbidity and mortality in lung transplant recipients (LTRs). However, data outlining use of echinocandins in prophylaxis and therapy of LTRs are limited. Method A single‐center retrospective cohort study on all LTRs from January‐2010 to December‐2016. Participants were screened for antifungal use to assess rate, tolerability, and clinical outcome of echinocandin use in LTRs, during the first 6 weeks of posttransplant. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…49 Concerning LgT, Al Jishi et al, in a single-center retrospective cohort study, investigated the use of echinocandin and concluded that it is an important second-line agent, still preempted by the azoles group, as LgT transplant recipient patients who received antifungal prophylaxis with azoles did not develop disseminated invasive aspergillosis, cryptococcal or endemic fungal infections. 50,51 The comparative studies mentioned in this subtopic on IFI prophylaxis in patients with SOT can be summarized and visualized in Table 2.…”
Section: Ifi Prophylaxis In Sotmentioning
confidence: 99%
“…49 Concerning LgT, Al Jishi et al, in a single-center retrospective cohort study, investigated the use of echinocandin and concluded that it is an important second-line agent, still preempted by the azoles group, as LgT transplant recipient patients who received antifungal prophylaxis with azoles did not develop disseminated invasive aspergillosis, cryptococcal or endemic fungal infections. 50,51 The comparative studies mentioned in this subtopic on IFI prophylaxis in patients with SOT can be summarized and visualized in Table 2.…”
Section: Ifi Prophylaxis In Sotmentioning
confidence: 99%
“…However, the use of intravenous systemic antifungal agents for primary prophylaxis after the early posttransplant hospitalization period is unpractical; despite that, these drugs are often considered as second-line agents due to their better safety profile when compared with triazoles. 2,6 Triazole antifungal agents are inhibitors of the synthesis of ergosterol, the main sterol in the fungal cell membrane. 26 These agents are the most frequently used class of drugs for systemic antifungal prophylaxis in LTx recipients, as their oral formulations favor long-term use, yet temporary parenteral administration is sometimes practiced in the early post-transplant period.…”
Section: Which Antifungal Drugs For Systemic Antifungal Prophylaxis?mentioning
confidence: 99%
“…1 Yeasts and moulds, in particular, are responsible for 15-35% of all post-transplant infections in LTx recipients and have high mortality rates. [2][3][4][5][6][7][8][9][10] Most fungal infections after LTx are caused by Aspergillus species (spp. ), the most frequent mold, and Candida species (spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have described the role of echinocandins for antifungal prophylaxis, and none to our knowledge have evaluated combination echinocandin and triazole antifungal prophylaxis in LTRs. 4,[18][19][20][21] The aim of this study was to analyze the effectiveness of a newly implemented institutional protocol utilizing the addition of perioperative anidulafungin to itraconazole prophylaxis compared to itraconazole prophylaxis alone in LTRs.…”
Section: Introductionmentioning
confidence: 99%